Repeatability and validity of different methods to determine the anaerobic threshold through the maximal multistage test in male cyclists and triathletes - Llodio, I.; Yanci, J.; Usandizaga, M.; Larrea, A.; Iturricastillo, A.; Cámara, J.; Granados, C. (Journal of Functional Morphology and Kinesiology, 2025)
Objectives: The aim of this study was to analyze the repeatability and validity of different methods to determine the anaerobic threshold through a maximal multistage cycling test;